A REVIEW: FACILE AND GREEN SYNTHESIS OF MARINE MACROALGAE AND ITS PHOTOCATALYTIC PERFORMANCE ON POLLUTED WATER REMEDIATION - ., Ramadhani; Said, Ahmad (Program Studi Akuakultur, Universitas Bangka Belitung, 2024)
This review critically examines the burgeoning field of research focused on the environmentally benign synthesis of metallic nanoparticles exploiting the unique properties and diverse array of marine macroalgae species. Harnessing macroalgal biomolecules as reductants and stabilizers, numerous findings have discovered the biosynthesis of silver, gold, iron oxide, zinc oxide, and other nanoparticles through a sustainable